2014
DOI: 10.1038/ncomms6244
|View full text |Cite
|
Sign up to set email alerts
|

Drp1 inhibition attenuates neurotoxicity and dopamine release deficits in vivo

Abstract: Mitochondrial dysfunction has been reported in both familial and sporadic Parkinson’s disease (PD). However, effective therapy targeting this pathway is currently inadequate. Recent studies suggest that manipulating the processes of mitochondrial fission and fusion has considerable potential for treating human diseases. To determine the therapeutic impact of targeting these pathways on PD, we used two complementary mouse models of mitochondrial impairments as seen in PD. We show here that blocking mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(170 citation statements)
references
References 71 publications
(139 reference statements)
14
156
0
Order By: Relevance
“…Recent studies with mdivi-1 (mitochondrial division inhibitor), a small molecule, selective inhibitor of DLP1 [17,86], revealed that inhibition of DLP1 exerts protective effects in heart and cerebral ischemiareperfusion models and provides neuroprotection in Parkinson models [30,129]. Mdivi-1 prevented mitochondrial fission, loss of mitochondrial membrane potential, and cell death in acute brain injury.…”
Section: Dlp1 Deficiencymentioning
confidence: 98%
“…Recent studies with mdivi-1 (mitochondrial division inhibitor), a small molecule, selective inhibitor of DLP1 [17,86], revealed that inhibition of DLP1 exerts protective effects in heart and cerebral ischemiareperfusion models and provides neuroprotection in Parkinson models [30,129]. Mdivi-1 prevented mitochondrial fission, loss of mitochondrial membrane potential, and cell death in acute brain injury.…”
Section: Dlp1 Deficiencymentioning
confidence: 98%
“…In addition to AD and HD, increased Drp1 activity and mitochondrial fission have also been observed in Parkinson's disease (PD). Dominant-negative inhibition of Drp1 in a PINK1 −/− mouse-knockout model of PD, as well as in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced Parkinsonism in mice, prevented neuronal death and rescued the impaired dopamine release that is associated with PD (Rappold et al, 2014). More recent work on the MPTP mouse model of PD supports these findings, as p110-TAT-peptidemediated inhibition of Drp1 localization to mitochondria attenuated the death of dopaminergic neurons (Filichia et al, 2016).…”
Section: Mitochondrial Dynamics In Neurodegenerative Diseasesmentioning
confidence: 99%
“…More recently inhibition of Drp1 has been tested in two Parkinson's disease models, a PINK1-/-mouse and a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) mouse model [ 94 ]. This study is important because it was demonstrated that mdivi-1 crosses the blood-brain barrier and in doing so was able to restore a striatal dopamine release defi cit and reduce neurotoxicity.…”
Section: Fission-fusion Compoundsmentioning
confidence: 95%